ETHNOBOTANICAL SURVEY OF ANTI-ASTHMATIC PLANTS IN SOUTH WESTERN NIGERIA - Sonibare, M. A.; Gbile, Z. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The paper presents the results of an ethnobotanical survey of plants used in the treatment of asthma in Ogun, Osun and Oyo states. Twenty markets were visited and forty-six plants belonging to thirty-three different families were collected. The plants’ families represented in the collection include, Amaryllidaceae, Apocynaceae, Combretaceae, Euphorbiaceae, Moraceae, Solanaceae, Zingiberaceae and others. Most of the herbs were prescribed along with other recipes, mono-prescription was rare. Modes of administration of the phytomedicines were concoction, decoctions and powdered ash residue.